Synthesis of hybrid polymer and its application as distributed feedback laser - Sahrul Hidayat; Fitrilawati; Bahtiar, A.; Siregar, R.E. (Universiti Kebangsaan Malaysia, 2013)
The hybrid inorganic-organic polymer was synthesized by sol-gel method from TMSPMA. Organic dye laser of DCM was added into hybrid polymer host matrices by means of solution method at room temperature. The distributed feedback (DFB) laser was fabricated from hybrid polymer-DCM film using Lloyd Mirror interference technique. The surface profile of device was observed using AFM. From the AFM image, we obtained that the grating period was about 385 nm and the depth of corrugation was about 60 nm. The characteristics of DFB laser was investigated by optical pumping using SHG Nd-YAG (λ=532 nm). The laser emission has been demonstrated at 582 nm with the spectral width (FWHM) less than 2 nm at pumping power of 14.00 mJ/pulse cm2. The experimental results have been confirmed by the theoretical model using coupled mode theory. The confirmation of experimental works by the theoretical model has a good result.